Effect of the Side Chains and Anode Material on Thermal Stability and Performance of Bulk-Heterojunction Solar Cells Using DPP(TBFu)2 Derivatives as Donor Materials. (29th December 2015) - Kovalenko, Alexander; Honová, Jana; Vala, Martin; Luňák, Stanislav; Fekete, Ladislav; Horáková, Petra; Dokládalová, Lenka; Kubáč, Lubomír; Weiter, Martin
Abstract : An optimized fabrication of bulk-heterojunction solar cells (BHJ SCs) based on previously reported diketopyrrolopyrrole donor, ethyl-hexylated DPP(TBFu)2, as well as two new DPP(TBFu)2 derivatives with ethyl-hexyl acetate and diethyl acetal solubilizing side-chains and PC60 BM as an acceptor is demonstrated. Slow gradual annealing of the solar cell causing the effective donor-acceptor reorganization, and as a result higher power conversion efficiency (PCE), is described. By replacing a hole transporting layer PEDOT:PSS with MoO3 we obtained higher PCE values as well as higher thermal stability of the anode contact interface. DPP(TBFu)2 derivative containing ethyl-hexyl acetate solubilizing side-chains possessed the best as-cast self-assembly and high crystallinity. However, the presence of ethyl-hexyl acetate and diethyl acetal electrophilic side-chains stabilizes HOMO energy of isolated DPP(TBFu)2 donors with respect to the ethyl-hexylated one, according to cyclic voltammetry.